Group Modelling Method in Web-Based Collaborative Learning Environment - Zhao, Jianhua; McConnell, David (Proceedings of the International Conference on Networked Learning, 2002)
Collaborative learning (Damon, 1984; Gabbert et al. 1986; Johnson and Johnson, 1989; Johnson et al. 1991; Kadell and Keehner, 1994; Kaye, 1991; Klemm, 1994; Webb, 1982) is the idea that small, interdependent groups of students work together as a team to help each other learn. So small learning group plays a very important role in collaborative learning process, especially in web-based collaborative learning environment. Many collaborative learning methods were explored and introduced by some researchers (Slavin, R., Sharan, S., Lazarowitz, R. H., Webb, C., and Schmuck, R., 1985; Slavin, R. E., 1995). To utilize collaborative learning approach in classroom-based environment also got a considerable success. But how to find an optimal approach to simulate collaborative learning process in web-based learning environment already became a question. Some researchers (Aiken, M. W., 1993; Klemm, W. R. & Snell, J. R., 1996; Dillenbourg, P., 1999; Tsoi, M. F., Goh, N. K. and Chia, L. S., 2000) already did a lot of work for it. The purpose of this research was focused on how to find an approach to simulate learning groups in web-based collaborative learning environments.